More than meets the eye: an eye-tracking experiment on the beauty contest game - Müller, Julia; Schwieren, Christiane (Discussion paper series, 2011)
The beauty contest game has been used to analyze how many steps of reasoning subjects are able to perform. A common finding is that a majority seem to have low levels of reasoning. We use eye-tracking to investigate not only the number chosen in the game, but also the strategies in use and the numbers contemplated. We can show that not all cases that are seemingly level-1 or level-2 thinking indeed are {they might be highly sophisticated adaptations to beliefs about other people's limited reasoning abilities.
Keywords: Arbeitspapier; Graue Literatur